Indigenous Perspectives and Gene Editing in Aotearoa New Zealand - Hudson, Maui; Mead, Aroha Te Pareake; Chagné, David; Roskruge, Nick; Morrison, Sandy; Wilcox, Phillip L.; Allan, Andrew C. (Frontiers in Bioengineering and Biotechnology, 2019)
Gene editing is arguably the most significant recent addition to the modern biotechnology toolbox, bringing both profoundly challenging and enabling opportunities. From a technical point of view the specificity and relative simplicity of these new tools has broadened the potential applications. However, from an ethical point of view it has re-ignited the debates generated by earlier forms of genetic modification. In New Zealand gene editing is currently considered genetic modification and is subject to approval processes under the Environmental Protection Authority (EPA). This process requires decision makers to take into account Māori perspectives. This article outlines previously articulated Māori perspectives on genetic modification and considers the continuing influence of those cultural and ethical arguments within the new context of gene editing. It also explores the range of ways cultural values might be used to analyse the risks and benefits of gene editing in the Aotearoa New Zealand context. Methods used to obtain these perspectives consisted of (a) review of relevant literature regarding lessons learned from the responses of Maori to genetic modification, (b) interviews of selected ‘key Maori informants’ and (c) surveys of self-selected individuals from groups with interests in either genetics or environmental management. The outcomes of this pilot study identified that while Māori informants were not categorically opposed to new and emerging gene editing technologies a priori, they suggest a dynamic approach to regulation is required where specific uses or types of uses are approved on a case by case basis. This study demonstrates how the cultural cues that Māori referenced in the genetic modification debate continue to be relevant in the context of gene editing but that further work is required to characterize the strength of various positions across the broader community.